Computational Chemistry to the Rescue: Modern Toolboxes for the Assignment of Complex Molecules by GIAO NMR Calculations1. Issue 35 (13th July 2016) - Grimblat, Nicolas; Sarotti, Ariel M.
Abstract: The calculations of NMR properties of molecules using quantum chemical methods have deeply impacted several branches of organic chemistry. They are particularly important in structural or stereochemical assignments of organic compounds, with implications in total synthesis, stereoselective reactions, and natural products chemistry. In studying the evolution of the strategies developed to support (or reject) a structural proposal, it becomes clear that the most effective and accurate ones involve sophisticated procedures to correlate experimental and computational data. Owing to their relatively high mathematical complexity, such calculations (CP3, DP4, ANN‐PRA) are often carried out using additional computational resources provided by the authors (such as applets or Excel files). This Minireview will cover the state‐of‐the‐art of these toolboxes in the assignment of organic molecules, including mathematical definitions, updates, and discussion of relevant examples. Abstract : Help ! The structural and stereochemical assignment of organic compounds is often a hard and difficult task. The calculation of NMR properties of molecules using quantum chemical methods has been extensively used in the recent past to settle the tridimensional structures of complex natural and unnatural products. In this Minireview, some recent advances in this area are presented and discussed.